A content analysis of the opinion columns of Luis D. Beltran and Terodoro F. Valencia during the first one hundred days of the Aquino government - Arboleda, Rainelda Jiffin I.; Umali, Violeda A. (University of the Philippines Diliman 1987)
This study is a content analysis of the opinion columns of Luis D. Beltran and Teodoro Valencia ("Straight from the Shoulder" and "Over a Cup of Coffee" respectively) during the first one hundred days of the government of President Corazon C. Aquino. These first one hundred days is commonly called a 'honeymoon' where the press-government relationship is concerned, since journalists usually refrain from writing critically about the President so as to give him/her breathing space and time to get used to his/her new responsibilities.

For this study, the 100 issues dated February 25, 1986 to June 4, 1986 comprised both the population and the sample for greater accuracy. Each day's column was studied and analyzed according to the style or manner in which it was written (either formal or informal), the subject matter or topics, and the slant taken by the columnist regarding the subject matter (whether critical or non-critical).

Out of the 96 columns written by Beltran during this period, 77 were written in a formal style while the rest (19 columns) were written in an informal manner, usually by means of a satire. Valencia, meanwhile, wrote all 100 of his columns in a formal style.

The topics written by both columnists were similar, with most of their column space devoted to the burning issues of the day. These included the controversies regarding the Officers-in-Charge; the Presidential Commission on Good Government; the activities of the different Cabinet [Ministers] and their ministries; and the policies and programs of the Aquino government.

On many topics, Beltran and Valencia had the same opinions. They were both critical of the manner in which the government replaced elective officials with their own appointed OICs' the sequestration powers of the PCGG; the policies set down by Labor Minister Augusto Sanchez; and the government's labor policies which seem to have scared away foreign investors.

There were, however, several topics on which the two columnists had differing views. Beltran was clearly approving of President Aquino while Valencia was more critical of her. As to Ferdinand Marcos, Valencia was more sympathetic to his situation while Beltran was vehemently critical of him.

The Marcos loyalists were given justifiable reasons by Valencia for their rallies while they were criticized by Beltran in his columns. The hidden wealth issue was exposed by Beltran while Valencia did not even mention it. Valencia also criticized the Constitutional Commission for being biased while Beltran gave it his approval.

US intervention in Philippine affairs was unanimously criticized by both columnists, as well as the bullying tactics which were called "People Power". The two columnists had different views regarding the Bataan Nuclear Power Plant, with Valencia calling for its operation and Beltran colling for its repudiation.

The two columnists were more ambiguous towards the Armed Forces of the Philippines, giving it almost the same number of criticisms and praises. Valencia, however, was very critical of the New People's Army and the Communists while Beltran did not even mention this group throughout the period of this study.
Thesis
Keywords: Beltran, Luis D. -- Criticism and interpretation; Valencia, Teodoro F. -- Criticism and interpretation; Press and politics -- Philippines; Content analysis (Communication)